Behavior of Highly Diluted Electrolytes in Strong Electric Fields—Prevention of Alumina Deposition on Grading Electrodes in HVDC Transmission Modules by CO2‐induced pH‐Control. Issue 38 (8th August 2014) - Weber, Immo; Mallick, Bert; Schild, Matthias; Kareth, Sabine; Puchta, Ralph; van Eldik, Rudi
Abstract Alumina deposition on platinum grading electrodes in high voltage direct current (HVDC) transmission modules is an unsolved problem that has been around for more than three decades. This is due to the unavoidable corrosion of aluminum heat sinks that causes severe damage to electrical power plants and losses in the range of a million Euro range per day in power outage. Simple experiments in a representative HV test setup showed that aluminates at concentrations even below 10−8 mol L−1 can deposit on anodes through neutralization by protons produced in de‐ionized water (κ≤0.15 μS cm−1) at 20–35 kV (8 mA) per electrode. In this otherwise electrolyte‐poor aqueous environment, the depositions are formed three orders of magnitude below the critical precipitation concentration at pH 7! In the presence of an inert electrolyte such as TMAT (tetramethylammonium‐p‐toluenesulfonate), at a concentration level just above that of the total dissolved aluminum, no deposition was observed. Deposition can be also prevented by doping with CO2 gas at a concentration level that is magnitudes lower than that of the dissolved aluminum. From an overview of aqueous aluminum chemistry, the mystery of the alumina deposition process and its inhibition by CO2 is experimentally resolved and fully explained by field accumulation and repulsion models in synergism with acid–base equilibria. The extraordinary size of the alumina depositions is accounted for in terms of proton tunneling through "hydrated" alumina, which is supported by quantum chemical calculations. As a consequence, pulse‐purging with pure CO2 gas is presented as a technical solution to prevent the deposition of alumina.